IDNLearn.com provides a collaborative platform for sharing and gaining knowledge. Get accurate and timely answers to your queries from our extensive network of experienced professionals.
Sagot :
[tex] \qquad \qquad \bf \huge\star \: \: \large{ \underline{Answer} } \huge \: \: \star[/tex]
- y = 1
[tex]\textsf{ \underline{\underline{Steps to solve the problem} }:}[/tex]
[tex] \qquad❖ \: \sf \:6 = 2(y + 2)[/tex]
[tex] \qquad❖ \: \sf \:(y + 2) = \cfrac{6}{2} [/tex]
[tex] \qquad❖ \: \sf \:y + 2 = 3[/tex]
[tex] \qquad❖ \: \sf \:y = 3 - 2[/tex]
[tex] \qquad❖ \: \sf \:y = 1[/tex]
[tex] \qquad \large \sf {Conclusion} : [/tex]
- Value of y = 1
Rewrite the equation as 2(y+2)=6
Divide each term in 2 (y+2)=6 by 2 and simplify
2(y+2)/2=6/2
Simplify the left side
Cancel the common factor of 2
x(y+3)x=6/2
Divide y+2 by 1
y+2=6/2
Simplify the right side
Divide 6 by 2
y+2=3
Move all terms not containing y to the right side of the equation
y=1
Divide each term in 2 (y+2)=6 by 2 and simplify
2(y+2)/2=6/2
Simplify the left side
Cancel the common factor of 2
x(y+3)x=6/2
Divide y+2 by 1
y+2=6/2
Simplify the right side
Divide 6 by 2
y+2=3
Move all terms not containing y to the right side of the equation
y=1
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is committed to your satisfaction. Thank you for visiting, and see you next time for more helpful answers.